Development of Enzyme Linked Immunosorbent Assay for humoral immuneresponse and infection monitoring of anthrax - NOURI, H. R.; RAZZAZ, H.; TAGHDIRI, M.; TADAYON, K.; BANIHASHEMI, S. R. (Journal of the Hellenic Veterinary Medical Society, 2020)
Immune assays were taken into consideration to diagnose and quantify metabolites such as antigen and antibody. Enzyme-Linked Immunosorbent Assays (ELISAs), which are used to detect antigens and antibodies, generated several periods of infectious and vaccination conditions. There is an extensive range of commercial infectious disease ELISA kits useful for the detection of human and animal IgG, IgA, IgM antibodies and microorganism antigens. Anthrax is one of the serious infectious diseases caused by rod-shaped, gram-positive bacteria known as Bacillus anthracis. Subunit or attenuated vaccines applied against anthrax disease increase the antibody against the Protective Antigen (PA) which has a critical role as a toxin of B. anthracis. Herein, the ELISA was developed using PA domain 4 and anthrax Lethal Factor to detect IgG antibody in serum. Besides, the level of anti-LF antibodies were determined as a complementary test to measure variance in antibody titers associated with vaccination or infection that leads to detection of anthrax in livestock. The results show that we developed high-quality ELISA kit that can be used to test immunogenicity of vaccines and infections in mice. We tried to develop the Anti- PA4 ELISA kit and conduct the validation studies to evaluate the fluctuation level of the antibody in the anthrax vaccine and distinction between disease and vaccination in mice.